ChemInform Abstract: Solvent‐ and Catalyst‐Free Regioselective Hydrophosphanation of Alkenes. Issue 7 (22nd February 2013) - Alonso, Francisco; Moglie, Yanina; Radivoy, Gabriel; Yus, Miguel
Abstract The title reaction, typically promoted by radicals or metal species, is shown to proceed in the absence of a catalyst, under solvent‐free conditions in a highly regioselective manner.